PREVALENCE OF ANAEMIA (REDUCED PACKED CELL VOLUME) AMONG PREGNANT WOMEN ATTENDING ANTENATAL CLINICS IN KATSINA METROPOLIS - Dibal, D. M.; Bashir, N. F.; Emere, M. C. (FUDMA JOURNAL OF SCIENCES, 2023)
Anaemia during pregnancy is still a major health problem in malaria endemic countries with clinical consequences including death of both mother and child. Moderate or severe anaemia during pregnancy may be associated with heavy parasitic infestation. This study investigated prevalence of anaemia among pregnant women attending antenatal clinics in Katsina metropolis, Katsina state. A cross-sectional study was carried out among 250 pregnant women attending four different public health centers in Katsina metropolis. Blood samples were obtained to determine their PCV. The PCV count was determined using hematocrit reader. The overall prevalence of anaemia for the all hospital was 110 (44.0%). The highest prevalence of anaemia 54 (84.38%) was recorded among pregnant women attending Turai Yar’adua Maternal and Children Hospital. The least prevalence of anaemia 14 (28.58%) was recorded among pregnant women attending PHC Kofar Marusa. A high prevalence of anaemia among pregnant women in this study was an indication of possible anaemia within the study area. This study advocates the need for pregnant women to undergo routine haemoglobin estimation and early malaria prophylaxis considering the deleterious effects of anaemia on them and their foetus.
Keywords: Anaemia; pregnant women; Antenatal clinic; Katsina; metropolis